Deficit cognitivo, biomarcadores endoteliais e mortalidade em pacientes em hemodiálise: um estudo de coorte prospectivo - Medeiros, Camilla Maroni Marques Freire de (2020)
Patients on hemodialysis have a higher prevalence of cognitive deficits, resulting in worse prognosis and higher mortality rates. Cardiovascular disease is the main cause of mortality in these patients. Endothelial lesion biomarkers are correlated with cardiovascular disease and mortality in this population. so far, we have not found studies evaluating the association between cognitive deficits and mortality from cardiovascular disease in patients undergoing hemodialysis. Objective: To evaluate the association between cognitive impairment and cardiovascular and noncardiovascular mortality and whether this possible association is independent of endothelial injury markers. Methodology: Prospective cohort study with 216 patients from 3 hemodialysis centers in the city of Fortaleza-CE, between June 2016 and June 2019 and followed for 30 months. Sociodemographic, clinical and laboratory data were obtained through questionnaires, patient interviews and electronic medical records. Cognitive function was accessed through the Cambridge Cognitive Examination (CAMCOG). Blood plasma samples were collected for the measurement of biomarkers VCAM-1, ICAM-1, Syndecan-1 and Angiopoietin -2 (AGPT2). Cox proportional hazards regression models were used to measure the association between cognitive function and each of the biomarkers with cardiovascular and non-cardiovascular mortality. Results: Cognitive function was associated with cardiovascular mortality (each 1 SD increase in cognitive function score associated with 69% lower risk of cardiovascular mortality (HR 0.31; 95% confidence interval [CI] 0.17-0.58), but was not associated with noncardiovascular mortality. Cognitive function was also associated with all markers of endothelial lesion except VCAM-1. There was also an association between ICAM-1, Syndecan -1 and AGPT2 with cardiovascular disease. The association between cognitive function and mortality cardiovascular disease remained significant, with no attenuation in HR value (adjusted HR 0.32 95% CI 0.16-0.59), after including each endothelial lesion biomarker individually in the Cox model. Conclusion: Cognitive function was associated with cardiovascular mortality but not with non-cardiovascular mortality. and this association cannot be explained by any of the endothelial lesion biomarkers.